2020
DOI: 10.3892/ol.2020.11478
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of MYH11 in lung cancer

Abstract: Myosin heavy chain 11 (MYH11), encoded by the MYH11 gene, is a protein that participates in muscle contraction through the hydrolysis of adenosine triphosphate. Although previous studies have demonstrated that MYH11 gene expression levels are downregulated in several types of cancer, its expression levels have rarely been investigated in lung cancer. The present study aimed to explore the clinical significance and prognostic value of MYH11 expression levels in lung cancer and to further study the underlying mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…It functions by stimulating effector cell functions and encouraging antitumor CD8+ T cells to enter tumors, aiding in the establishment of anti-tumoral memory ( Skeate et al, 2020 ). MYH11 encodes a protein that participates in muscle contraction through the hydrolysis of adenosine triphosphate; its expression levels are downregulated in several types of cancers ( Alhopuro et al, 2008 ; Nie et al, 2020 ). NRXN1 encodes a transmembrane protein that functions as a cell adhesion molecule in synaptic transmission ( Reissner et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…It functions by stimulating effector cell functions and encouraging antitumor CD8+ T cells to enter tumors, aiding in the establishment of anti-tumoral memory ( Skeate et al, 2020 ). MYH11 encodes a protein that participates in muscle contraction through the hydrolysis of adenosine triphosphate; its expression levels are downregulated in several types of cancers ( Alhopuro et al, 2008 ; Nie et al, 2020 ). NRXN1 encodes a transmembrane protein that functions as a cell adhesion molecule in synaptic transmission ( Reissner et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have revealed that MYH11 is a biomarker of BLCA (15,17), which is consistent with our conclusion. Additionally, the expression level of MYH11 has been reported to be dysregulated in colorectal cancer (33,34), lung cancer (35), laryngeal cancer (36) and acute myeloid leukemia (37). Based on these researches above mentioned, we speculate that myosin-dependent contractile activity in nonmuscle cells may be participated in cell adhesion and migration to promote tumor invasion.…”
Section: Discussionmentioning
confidence: 84%
“…Evidences for c-FOS overexpression as promoting apoptosis and delaying ovarian cancer progression in preclinical models may be supported by the findings in these clinical specimens [ 19 ]. MYH11 expression has been shown to be downregulated in cancers, and its downregulation corresponds to poor prognosis and survival [ 20 ].…”
Section: Resultsmentioning
confidence: 99%